2020
DOI: 10.3390/cells9092080
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomopathies: New Therapeutic Perspectives

Abstract: Ribosomopathies are a group of rare diseases in which genetic mutations cause defects in either ribosome biogenesis or function, given specific phenotypes. Ribosomal proteins, and multiple other factors that are necessary for ribosome biogenesis (rRNA processing, assembly of subunits, export to cytoplasm), can be affected in ribosomopathies. Despite the need for ribosomes in all cell types, these diseases result mainly in tissue-specific impairments. Depending on the type of ribosomopathy and its pathogenicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 146 publications
(167 reference statements)
1
9
0
Order By: Relevance
“…This includes chronic blood transfusions followed by steroids to allow patients to survive this disease phase (Table 2), but with many undesirable and even fatal side effects after long-term of steroids, including hypertension, diabetes mellitus, and growth retardation. 257 There is clearly an unmet need in developing new therapeutic strategies for ribosomopathies.…”
Section: The Molecular Basis Of Ribosomopathiesmentioning
confidence: 99%
“…This includes chronic blood transfusions followed by steroids to allow patients to survive this disease phase (Table 2), but with many undesirable and even fatal side effects after long-term of steroids, including hypertension, diabetes mellitus, and growth retardation. 257 There is clearly an unmet need in developing new therapeutic strategies for ribosomopathies.…”
Section: The Molecular Basis Of Ribosomopathiesmentioning
confidence: 99%
“…L-leucine, a branch chain amino acid, is a potential emerging treatment for DBA, and other ribosomopathies, that upregulates ribosome biosynthesis via the mTOR signaling pathway and targets the underlying RP dysfunction ( Payne et al, 2012 ; Xu et al, 2016 ; Orgebin et al, 2020 ). In a recent study, L-leucine treatment resulted in erythroid responses in a small number of transfusion-dependent patients with DBA, and improved weight gain and linear growth velocity in a larger number of patients ( Vlachos et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ribosomes are comprised of ribonucleoprotein and non-coding ribosomal RNAs in eukaryotes and are conserved molecular structures required for protein synthesis [26]. Cancer development and progression are associated with ribosomal dysregulation, which affects the expression of key factors involved in tumorigenesis [27]. It has been reported that a single ribosomal assembly factor promotes LUAD progression through the Notch signaling pathway [28].…”
Section: Discussionmentioning
confidence: 99%